Biventricular Levitronix CentriMag Assist Device: A “Bridge to Recovery” Solution in Patients with Acute Fulminant Myocarditis - Vollroth, Marcel (Hindawi Publishing Corporation, 2012)
Fulminant myocarditis (FM) represents a crucial cardiac pathology with extensive hemodynamic compromise occurring in a previously healthy patient. Early death occurs because of acute cardiac decompensation from inflammation, necrosis, and myocytolysis. Nevertheless, in this situation implantation of an extracorporeal circulatory support system may ensure cardiac recovery. We herein report our experience using a biventricular Levitronix CentriMag system for bridge to recovery.